2010
DOI: 10.4142/jvs.2010.11.2.169
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of stable cell lines constitutively expressing the porcine reproductive and respiratory syndrome virus nucleocapsid protein

Abstract: Despite global efforts to control porcine reproductive and respiratory syndrome virus (PRRSV) infection, the virus continues to cause economic problems in the swine industry worldwide. In this study, we attempted to generate and characterize a panel of stable BHK cell lines that constitutively express the nucleocapsid (N) protein of type 1 or type 2 PRRSV. The established BHK cell lines were found to react well with N-specific antibodies as well as the hyperimmune serum of pigs raised against each genotype of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Briefly, MARC-145 cells were seeded in 96-well cell culture plates and infected with CA-2-12 or CA-2-100 for 24 h at 37 C in a 5% CO 2 incubator. The virus-infected cells were fixed and subsequently subjected to IPMA using serial 2-fold dilutions of the sera (starting dilution 1:4) as described previously (Decorte et al, 2014;Sagong et al, 2010). The results were determined by examination with a light microscope (Leica, Wetzlar, Germany), and the IPMA titer was calculated as the highest dilution of serum giving PRRSV-specific cytoplasmic staining of infected MARC-145 cells.…”
Section: Prrsv Serologymentioning
confidence: 99%
“…Briefly, MARC-145 cells were seeded in 96-well cell culture plates and infected with CA-2-12 or CA-2-100 for 24 h at 37 C in a 5% CO 2 incubator. The virus-infected cells were fixed and subsequently subjected to IPMA using serial 2-fold dilutions of the sera (starting dilution 1:4) as described previously (Decorte et al, 2014;Sagong et al, 2010). The results were determined by examination with a light microscope (Leica, Wetzlar, Germany), and the IPMA titer was calculated as the highest dilution of serum giving PRRSV-specific cytoplasmic staining of infected MARC-145 cells.…”
Section: Prrsv Serologymentioning
confidence: 99%
“…Customarily, an IPMA is used to monitor antigen by inoculating viruses into cells (Khudyakov Yu et al, 1994;Direksin et al, 2002;Guedes et al, 2002), which involves complicated procedures and unstable antigen content. A recent study suggested that cells stably expressing the major viral antigen could be used for IPMA (Sagong et al, 2010). In the present study, we developed an IPMA for the detection of swHEV antibodies using modified HepG2 cell lines that stably expressed the ORF3 protein as a diagnostic target.…”
Section: Discussionmentioning
confidence: 99%
“…Radlett et al [11] greatly improved the growth conditions of BHK-21 cells in suspension culture demonstrating the usefulness of BHK-21 cells for the commercial production of viral vaccines for animals. After that, cell lines have been used for virus detection and production of virus and recombinant proteins in many laboratories throughout the world [12][13][14][15][16]. Cultivation of the BHK cells in submerged systems similar to microorganisms may well be considered an advance for industrial use of animal cells.…”
Section: Introductionmentioning
confidence: 99%